A Systematic Review of the Outcome of Child Abuse in Long-Term Care. (October 2020) - Carr, Alan; Duff, Hollie; Craddock, Fiona
The aim of the systematic review described in this article was to determine the outcome of child maltreatment in long-term childcare and the scope of the evidence base in this area. Searches of 10 databases were conducted. Forty-nine documents describing 21 primary studies and 25 secondary studies were selected for review. Searches, study selection, data extraction, and study quality assessments were independently conducted by two researchers, with a high degree of interrater reliability. Participants in the 21 primary studies included 3, 856 abuse survivors and 1, 577 nonabused controls. In six primary studies, survivors were under 18 years, and participants in the remaining primary studies were adults with a mean age of 54 years. Reviewed studies were conducted in the United Kingdom, the United States, Finland, Romania, Tanzania, Canada, Ireland, Australia, the Netherlands, Germany, Austria, and Switzerland. Participants were abused in religious and nonreligious residential care centers and foster care. There were significant associations between the experience of child abuse in long-term care and adjustment across the life span in the domains of mental health, physical health, and psychosocial adjustment. Evidence-based trauma-focused treatment should be offered to child abuse survivors. Future research in this area should prioritize longitudinal studies.